Effect of Leaf Extracts of Lantana Camara L. on Germination and Growth of Some Crops Species (Saptagandaki Journal, 2022)
Allelopathy is a biotic interaction between plants where one plant inhibits the germination and growth of other plants by releasing certain allelochemicals. In this research we evaluated the allelopathic effect of aqueous leaf extract of Lantana camara on the germination and growth of four crop plants. The experiment was conducted in sterilized petri dishes in Botany lab of Saptagandaki Multiple Campus, Bharatpur, Chitwan, Nepal. The effect of different concentrations of extracts was studied and compared with the control. The results revealed that the germination and seedling growth of all species were significantly inhibited at different concentrations as compared to the control. The lowest germination percentage and seedling growth was found in Brassica campestris and Oryza sativa plant respectively and effect was least in Triticum aestivum plant at 10% concentration. The germination percentages, seedling growth and, biomass in all species were observed to reduce, with the increasing concentration of aqueous extracts. The study concluded that Lantana camara leaf extract allelochemicals have adverse effects on germination, seedling growth and dry matter accumulation of all tested crops.